Kako pripraviti študenta na inkluzivno šolo: evalvacija novega modela nastopov pri didaktiki družboslovja - Umek, Maja; Raztresen, Marjeta (Revija za elementarno izobraževanje, 2011)
How to Prepare Students for Inclusive Schools : Evaluation of a New Model of Pedagogical Praxis within the Didactics of Social Science. Inclusive schools emphasize the optimal development of all students. The teaching process starts with each individual student, where their developmental, social and cultural features are taken into consideration. In recent years, the planning and management of the inclusive approach to teaching has been one of the main aims - and also problems - of student teachers when they undergo their practical pedagogical training in the didactics of social sciences. We found that one of the reasons for these problems is the classical orientation and organization of student teacher observation and the demonstration lessons. With this in mind, we invented a new model of pedagogical praxis within the didactics of social science. In this article we present this model and the first evaluation of its use conducted by student teachers, teacher mentors and lecturers who work and study the didactics of social science.
Keywords: inclusive school; inclusion; didactics of social science; pupils with special needs; pedagogical praxis